Phytotoxic effects of metabolites from Alternaria euphorbiicola against its host plant Euphorbia heterophylla - Varejão,Eduardo Vinícius Vieira (2013)
A bioassay-guided fractionation of culture filtrates of the fungus Alternaria euphorbiicola, a pathogen of the weed Euphorbia heterophylla, led to the isolation of anhydromevalonolactone (1), tyrosol (2), (R)-( - )-mevalonolactone (3), and cycloglycylproline (4). When tested on the punctured leaves of the host plant, these compounds produced bleached lesions with dark brown margins at concentrations as low as 80 µM. When tested on the leaves of other relevant weeds, only cycloglycylproline showed selective activity against E. heterophylla. This is the first report on the isolation of phytotoxins from A. euphorbiicola and on the phytotoxicity of anhydromevalonolactone, (R)-( - )-mevalonolactone, and cycloglycylproline.